Graphene petal foams with hierarchical micro- and nano-channels for ultrafast spontaneous and continuous oil recovery. Issue 21 (12th May 2022) - Wu, Shiwen; Tian, Siyu; Jian, Ruda; Wu, Ting-Nan; Milazzo, Tye David; Luo, Tengfei; Xiong, Guoping
Abstract : Hierarchical micro- and nano-channels for ultrafast spontaneous and continuous oil recovery. Abstract : Marine oil contamination remediation remains a worldwide challenge. Siphon action provides a spontaneous, continuous, low-cost and green route for oil recovery. However, it is still limited by the low oil recovery rate due to insufficient internal pathways for oil transport. In this paper, a graphene petal foam (GPF)-based oil skimmer is designed and fabricated by plasma-enhanced chemical vapor deposition (PECVD) for ultrafast self-pumping oil recovery from oil/water mixtures. The hierarchical structure, containing micro- and nano-channels formed by interconnected graphene networks and vertically aligned graphene petals (GPs), respectively, and micro-pores inherited from the 3D interconnected structure of Ni foam, provides multiple fast passages for oil transport. An oil recovery rate of 135.2 L m −2 h −1 is achieved in dark conditions for such oil skimmers, while the value is increased to 318.8 L m −2 h −1 under solar irradiation of 1 kW m −2 because of the excellent solar-heating effect of GPs. Quantitative analyses suggest that 68.8% of such a high oil recovery rate is contributed by the nano-channels and micro-pores, while 31.2% arises from the micro-channels. Our demonstrated GPF oil skimmers exhibit great promise for fast spontaneous and continuous oil contamination cleanup.